New approach for mobile ad‐hoc networks unity issue in a suspicious environment. Issue 1 (1st March 2013) - Khosravi, Adle; Kavian, Yousef Seifi
Abstract : This study investigates the problem of unity in a mobile ad‐hoc network (MANET) when the members are suspected of having malicious faults. This study has reexamined the related Byzantine agreement (BA) problem for the new territory of MANET. The authors provide a new fault modelling approach followed by a new algorithm for the BA problem considering the limited connectivity of MANET. The proposed protocol results in a significant save in packet transmission counts for a fault‐free member to reach an agreement in comparison with previous studies. Also, the minimum required network connectivity is reduced in this study to cover more network topologies. The proposed protocol also distinguishes faulty transmission media from a faulty processor which increases the maximum number of allowable faulty units in the network. Simulation results are provided to depict the applicability of the proposed protocol in mobile networks.